Radiation Driven Chemistry in Biomolecules—is (V)UV Involved in the Bioactivity of Argon Jet Plasmas? - Bruno, G.; Wenske, S.; Mahdikia, H.; Gerling, T.; von Woedtke, T.; Wende, K. (Frontiers in Physics, 2021)
Cold physical plasmas, especially noble gas driven plasma jets, emit considerable amounts of ultraviolet radiation (UV). Given that a noble gas channel is present, even the energetic vacuum UV can reach the treated target. The relevance of UV radiation for antimicrobial effects is generally accepted. It remains to be clarified if this radiation is relevant for other biomedical application of plasmas, e.g., in wound care or cancer remediation. In this work, the role of (vacuum) ultraviolet radiation generated by the argon plasma jet kINPen for cysteine modifications was investigated in aqueous solutions and porcine skin. To differentiate the effects of photons of different wavelength and complete plasma discharge, a micro chamber equipped with a MgF2, Suprasil, or Borosilicate glass window was used. In liquid phase, plasma-derived VUV radiation was effective and led to the formation of cysteine oxidation products and molecule breakdown products, yielding sulfite, sulfate, and hydrogen sulfide. At the boundary layer, the impact of VUV photons led to water molecule photolysis and formation of hydroxyl radicals and hydrogen peroxide. In addition, photolytic cleavage of the weak carbon-sulfur bond initiated the formation of sulfur oxy ions. In the intact skin model, protein thiol modification was rare even if a VUV transparent MgF2 window was used. Presumably, the plasma-derived VUV radiation played a limited role since reactions at the boundary layer are less frequent and the dense biomolecules layers block it effectively, inhibiting significant penetration. This result further emphasizes the safety of physical plasmas in biomedical applications.